ANALISIS KANDUNGAN FORMALIN PADA CABE MERAH GILING YANG DIJUAL DI PASAR TRADISIONAL KOTA JAMBI - Havizur Rahman; Dika Zamri Yanni; Putri Maya Sari; Mia Prajuwita; Intan Lestari (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2019)
Research has been conducted to analyze the presence of formaldehyde content in ground red chili which is sold in the traditional markets of Jambi city. The milled red chili samples were obtained from 5 markets and each market was chosen by 5 milled red chili traders. Stages in this study include sample preparation, a qualitative test of formaldehyde content using chromatophenic acid reagents, and quantitative analysis of formalin using UV-Vis spectrophotometer at a wavelength of 566 nm. The results of this study showed 6 of the 25 samples identified to contain formalin. Qualitative analysis with chromatophenic acid reagents showed a change in color to brown. Formalin levels for positive samples included A2 samples at 0.54 g / kg, B4 at 0.74 g / kg, C2 at 0.56 g / kg, D3 at 0.65 g / kg, E3 at 0.53 g / kg, and E4 of 0.65 g / kg. It can be concluded that the discovery of formaldehyde content in ground red chili at several points in the traditional markets of the city of Jambi.